2021
DOI: 10.1371/journal.pntd.0009462
|View full text |Cite
|
Sign up to set email alerts
|

Mapping survey of schistosomiasis and soil-transmitted helminthiases towards mass drug administration in The Gambia

Abstract: Background A national mapping survey of schistosomiasis (SCH) and soil-transmitted helminthiases (STH) was conducted in The Gambia in May, 2015. The survey aimed at establishing endemicity of schistosomiasis and soil-transmitted helminthiases to inform decisions on program planning and implementation of mass drug administration (MDA). Methodology/Principal findings A cross-section of 10,434 eligible school aged children (SAC), aged 7 to 14 years old were enrolled in the survey. The participants were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 6 publications
6
16
1
Order By: Relevance
“…haematobium infection in B . senegalensis observed in this study corresponds to the prevalence of urogenital schistosomiasis infection observed in humans in these regions [ 6 , 7 , 30 ]. In recent studies on human populations, urogenital schistosomiasis was more common in CRR than URR.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…haematobium infection in B . senegalensis observed in this study corresponds to the prevalence of urogenital schistosomiasis infection observed in humans in these regions [ 6 , 7 , 30 ]. In recent studies on human populations, urogenital schistosomiasis was more common in CRR than URR.…”
Section: Discussionsupporting
confidence: 57%
“…Bulinus senegalensis , the most widely distributed of all the Bulinus species in this study, was the only snail found infected with the human parasite, Schistosoma haematobium , albeit at just four study sites (3 in CRR and 1 in URR). These sites are in communities (Jahanka, Njoren Sare Jabel and Dingiri) that are known hotspots of urogenital schistosomiasis [ 7 , 30 ]. The rate of S .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations